Frequency of Hepatitis B and Hepatitis C Seropositivity Among Repeatedly Transfused Thalassemic Children (Medical Forum Monthly, 2020)
Objective: To determine the frequency of Hepatitis B and Hepatitis C seropositivity among repeatedly transfused thalassaemic children at a tertiary care hospital in Punjab.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Paediatrics, Poonch Medical College Rawalakot from March 2016 to September 2016.Materials and Methods: This study involved 300 children of both genders aged between 2-12 years presenting with beta-Thalassemia Major having ≥10 transfusions at the time of presentation. A written informed consent was taken from parents of each patient before they underwent laboratory testing for hepatitis B and C. Various social and demographic factors were also related with the seropositivity of both the visruses.Results: Mean age of the patients were 6.95±3.19 years. There were 169 (56.3%) male and 131 (43.7%) female patients in the study group. The number of transfusions ranged from 10 to 149 with a mean of 70.55±39.31. 31 (10.3%) children were seropositive for hepatitis B. The frequency of Hepatitis B seropositivity increased significantly with increasing age of the patient and with increasing number of transfusions. 128 (42.7%) children were seropositive for hepatitis C. The frequency of Hepatitis C seropositivity increased significantly with increasing age of the patient and with increasing number of transfusions.Conclusion: The frequency of Hepatitis B and C seropositivity was found to be 10.3% and 42.7% respectively among repeatedly transfused thalassaemic children presenting at a tertiary care hospital in Punjab. The frequency increased significantly with increasing age of the patient and number of transfusions received before presentation.